Yield of six grasses cultivated by grazing under effect of different nitrogen fertilization and annual seasons Produção de seis capins manejados por pastejo sob efeito de diferentes doses nitrogenadas e estações anuais - Fernando França da Cunha; José Luis Aguiar Figueiredo; Carlos Eugênio Martins; Antônio Carlos Cóser; Rubens Alves de Oliveira; Carlos Augusto Brasileiro de Alencar; Paulo Roberto Cecon; Brauliro Gonçalves Leal (Revista Brasileira de Saúde e Produção Animal, 2010)
Dry matter yield of six irrigated grasses cultivated by grazing under different nitrogen fertilization and annual seasons in Brazil. The experiment was conducted in a split plot design, tends a factorial design 4 x 6 (nitrogen and grasses) in the plots and season (autumn/winter and spring/summer) in the split-plots, in a completely randomized block, with four repetitions. The nitrogen doses were of 100; 300; 500 and 700kg/ha/ano and the grasses were: Xaraes, Mombaça, Tanzania, Pioneiro, Marandu and Estrela. The irrigation system was semi-fixed conventional sprinkling. The dry matter yield was obtained by means of the dry material in ventilated stoves at 60°C, for 72h. The appraised grasses presented different dry matter yield. The factor temperature was the responsible for the differences among seasons. The increase of the nitrogen fertilizer did not affect the dry matter yield due to methodology for its determination and for the degradation of the physical quality of the soil. It was observed, in the general, that the Xaraes, Tanzania and Mombaça presented larger, and Pioneiro, smaller dry matter yield, respectively. The highest temperatures happened in the spring/summer season and provided larger dry matter yield. The nitrogen fertilization did not influence the dry matter yield of the appraised grasses. Objetivou-se avaliar a produtividade de matéria seca de seis capins irrigados manejados por pastejo sob efeito de diferentes adubações nitrogenadas e estações anuais na região Leste do estado de Minas Gerais. O experimento foi conduzido em parcelas subdivididas, com um esquema fatorial 4 x 6 (doses de nitrogênio e capins), e nas subparcelas as estações do ano (outono/inverno e primavera/verão) foram avaliadas no delineamento em blocos casualizados, com quatro repetições. As doses nitrogenadas foram de 100; 300; 500 e 700kg/há/ano, e os capins foram Xaraés, Mombaça, Tanzânia, Pioneiro, Marandu e Estrela. O sistema de irrigação utilizado foi aspersão convencional semifixo. A produtividade foi obtida por meio do material seco em estufa ventilada a 60°C, por 72h. Os capins avaliados apresentaram diferentes produtividades de matéria seca. O fator temperatura foi o responsável pelas diferenças encontradas entre estações. O aumento da dose nitrogenada não afetou a produtividade de matéria seca devido à metodologia para sua determinação e pela degradação da qualidade física do solo. Os capins Xaraés, Tanzânia e Mombaça apresentaram maiores, e o Pioneiro apresentou menor produtividade de matéria seca, respectivamente. As maiores temperaturas ocorridas na estação primavera/verão proporcionaram maior produtividade de matéria seca. A adubação nitrogenada não influenciou as produtividades dos capins avaliados.